The Use of Position Check Tracking Techniques in Revealing the Perpetrators of Theft at the Lamongan Police (Indonesian Journal of Police Studies, 2024)
This research is motivated by the importance of using track and trace techniques to determine the location of vehicle theft perpetrators through the perpetrator's phone number, in order to facilitate the process of capturing them. The aim of this research is to describe the mechanism of using track and trace in capturing vehicle theft perpetrators and the collaboration between the Criminal Investigation Unit of the Lamongan Police Resort and external agencies in arresting vehicle theft perpetrators using track and trace, as well as identifying factors that can hinder the use of track and trace in capturing vehicle theft perpetrators. The findings of this research indicate that the use of indirect position checks does not directly provide the location of the perpetrator, but rather the location of the BTS towers around the perpetrator. Additionally, the collaboration involved units from other district criminal investigation units, local network operators, and the Department of Population and Civil Registration, which, in practice, lacked a clear memorandum of understanding. The use of position checks faces inhibiting factors, such as insufficient member capabilities, the absence of tools like direct finders, perpetrators changing their phone numbers, and perpetrators predominantly using 4G networks with extensive coverage. From these findings, it can be concluded that there are many factors hindering the implementation of position checks, hence efforts are needed to ensure its optimal execution, such as conducting regular training activities, establishing SOPs related to position check usage to prevent misuse, and establishing memoranda of understanding with collaborating agencies.
Keywords: Position Check, Vehicle Theft, Arrest